An immunocytochemical and in situ hybridization analysis of annexin 1 expression in rat mast cells: Modulation by inflammation and dexamethasone - Oliani, Sonia M. [UNESP]; Christian, Helen C.; Manston, John; Flower, Roderick J.; Perretti, Mauro (Elsevier, 2000)
The presence and localization of the anti-inflammatory protein annexin 1 (also known as lipocortin 1) in perivenular rat mast cells was investigated here. Using the rat mesenteric microvascular bed and a combination of morphologic techniques ranging from immunofluorescence to electron microscopy analyses, we detected the presence of annexin 1 in discrete intracellular sites, both in the nucleus and in the cytoplasm. In resting mast cells, most of the protein pool (approximately 80% of the cytosolic portion) was localized to cytoplasmic granules. In agreement with other cell types, treatment of rats with dexamethasone (0.2 mg/kg, ip) increased annexin 1 expression in mast cells, inducing a remarkable appearance of clusters of protein immunoreactivity. This effect was most likely the result of de novo protein synthesis as determined by an increase in mRNA seen by in situ hybridization. Triggering an ongoing experimental inflammatory response (0.3 mg of carrageenin, ip) increased annexin 1 mRNA and protein levels. In conclusion, we report for the first time the localization of annexin 1 in connective tissue mast cells, and its susceptibility not only to glucocorticoid hormone treatment, but also to an experimental acute inflammatory response.